2014
DOI: 10.1371/journal.pone.0088069
|View full text |Cite
|
Sign up to set email alerts
|

The NRF2-KEAP1 Pathway Is an Early Responsive Gene Network in Arsenic Exposed Lymphoblastoid Cells

Abstract: Inorganic arsenic (iAs), a major environmental contaminant, has risen as an important health problem worldwide. More detailed identification of the molecular mechanisms associated with iAs exposure would help to establish better strategies for prevention and treatment. Although chronic iAs exposures have been previously studied there is little to no information regarding the early events of exposure to iAs. To better characterize the early mechanisms of iAs exposure we conducted gene expression studies using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Consistent with previous results [14], As treatment greatly induced Nrf2 protein content in MEL cells, and subsequentially increased the luciferase reporter activity of pGL3/ARE (an established construct to assay the transcriptional activity of Nrf2 [55]) in MEL cells ( Fig. 3E, Po 0.05).…”
Section: Nrf2 Transcriptionally Drives Mir-214 Expressionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous results [14], As treatment greatly induced Nrf2 protein content in MEL cells, and subsequentially increased the luciferase reporter activity of pGL3/ARE (an established construct to assay the transcriptional activity of Nrf2 [55]) in MEL cells ( Fig. 3E, Po 0.05).…”
Section: Nrf2 Transcriptionally Drives Mir-214 Expressionsupporting
confidence: 92%
“…The important role of Nrf2 in anti-stress responses has also been documented in erythroid cells [14,71]. Although evidence suggested that ATF4 could interact with Nrf2 to regulate the expression of antioxidant enzymes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, arsenic occurred most frequently in conjunction with “signaling by GPCR” and “GPCR downstream signaling”, with a combined 225 co-occurrences and an approximate 1.4% chance co-occurrence, and less than 2.3% chance respectively. Arsenic exposure also had a high number of co-occurrences with more specific signaling transduction pathways such as T-cell receptor signaling (28 co-occurrences, 1% probability) 19 and B-cell receptor signaling (36 co-occurrences, 1.2% probability), 20 both of which have been supported by scientific literature.…”
Section: Qualitative Observations Biomedical Implications and Discumentioning
confidence: 66%
“…In addition, the Ectodermal‐Neural Cortex 1 (ENC1) gene, a negative regulator of NRF2 (Wang and Zhang, ), was also found down‐regulated by ZGA (Supplementary Materials S1 and 2). The Nrf2‐mediated oxidative stress response pathway has been shown to play an important role in protecting cells against oxidative damage and promoting detoxification (Cordova et al, ). Nrf2 has been shown to aid in the acute wound healing process by regulating inflammation and promoting survival of keratinocytes under stress conditions (Braun et al, ).…”
Section: Discussionmentioning
confidence: 99%